Perceived Discrimination, Coping Strategies, and Mexican Origin Adolescents’ Internalizing and Externalizing Behaviors: Examining the Moderating Role of Gender and Cultural Orientation - Brittian, Aerika S. (2013)
The literature identifying effective coping strategies related to perceived discrimination has yielded mixed findings, suggesting that recommendations for effective coping may vary by individual and group differences. The current study examined the influence of perceived discrimination and coping strategies on Mexican origin adolescents’ later internalizing symptoms and externalizing behaviors, and assessed the moderating roles of gender and cultural orientation. Participants included 189 adolescents (46% male, 54% female) interviewed at 7(th) and 8(th) grade. Results suggested that the associations between perceived discrimination and internalizing symptoms were buffered by distraction coping among youth that were low on Anglo orientation but not among youth high on Anglo orientation. In addition, the associations between perceived discrimination and externalizing behaviors were buffered by social support seeking, but only among youth that were low on Mexican orientation. Directions for future research and application of the current research are discussed.